2022
DOI: 10.34172/jpd.2022.11154
|View full text |Cite
|
Sign up to set email alerts
|

Defining vitamin D deficiency in patients with sickle cell disease; A meta-analysis

Abstract: Introduction: Sickle cell disease (SCD) is one of the hereditary blood disorders that affects the red blood cells. Several lines of evidence indicated that the vitamin D deficiency (VDD) is quite common in children with SCD and vitamin D supplementation enhanced health-related quality of life in these patients. The present study is aimed to assess the exact prevalence of VDD in SCD patients using meta-analysis. Materials and Methods: A systematic search was conducted in PubMed and Google Scholar to extract the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…al., 2022). The results of a meta-analysis of 26 studies revealed that the global prevalence of VD deficiency in SCD is 60%(Sahu et al, 2022). This deficiency could arise from multiple factors in this population, one being, diminished nutrient absorption caused by intestinal mucosa damage(Mandese et al, 2019).…”
mentioning
confidence: 99%
“…al., 2022). The results of a meta-analysis of 26 studies revealed that the global prevalence of VD deficiency in SCD is 60%(Sahu et al, 2022). This deficiency could arise from multiple factors in this population, one being, diminished nutrient absorption caused by intestinal mucosa damage(Mandese et al, 2019).…”
mentioning
confidence: 99%